2020
DOI: 10.3390/ma13102342
|View full text |Cite
|
Sign up to set email alerts
|

Purification for Carbon Nanotubes Synthesized by Flame Fragments Deposition via Hydrogen Peroxide and Acetone

Abstract: Carbon nanotubes (CNTs) are synthesized by the flame fragment deposition (FFD) technique using Iraqi liquefied petroleum gas (LPG) as a source of carbon in a hand-made reactor at a low temperature (160 °C) without using a catalyst. Purification of the multi-walled carbon nanotubes (MWCNTs) is carried out using a two-step process consisting of sonication in 30 wt.% hydrogen peroxide (H2O2) solution at room temperature to remove amorphous impurities adhering to the walls of the CNTs and carbon nanoparticles (CNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…No other peaks related to impurities were detected in both cases, which confirms the high purity of these materials in terms of BN and carbon, respectively. Similar XRD patterns for high-purity BNNTs and CNTs have been reported in recent studies [17,18].…”
Section: Microstructure and Surface Chemistrysupporting
confidence: 86%
“…No other peaks related to impurities were detected in both cases, which confirms the high purity of these materials in terms of BN and carbon, respectively. Similar XRD patterns for high-purity BNNTs and CNTs have been reported in recent studies [17,18].…”
Section: Microstructure and Surface Chemistrysupporting
confidence: 86%
“…In the region 5–50° (2θ), complexes 1 ( a – c ), and 1g showed sharp diffraction patterns, suggesting that the complexes exist in a crystalline structure. While complexes 1 ( d – f ), and 1h showed very few diffraction peaks, they indicated that the complexes were between crystalline and amorphous phases [ 42 ]. The crystallite sizes of the samples were evaluated using Scherrer’s equation [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…1. The method used in the purification of the CNTs that have been synthesized in this section is a modification of the method described in previous work 11 . Purification of the CNTs that have been synthesized was accomplished in this manner by calcination at 350 C for 2 hours, followed by oxidation with hydrogen peroxide H 2 O 2 , followed by treatment with acetone.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon nanotubes can be created using a variety of techniques, including laser ablation LA, arc discharge AD, chemical vapor deposition (CVD) and flame fragments deposition (FFD) 10,11 . Most CNT synthesis procedures result in CNTs that are combined with graphitic nanoparticles, catalytic particles, and amorphous carbon are examples of amorphous and crystalline impurities.…”
Section: Introductionmentioning
confidence: 99%